Perylene-based molecular device: multifunctional spintronic and spin caloritronic applications. Issue 10 (24th February 2023) - Wu, Xuming; Xiao, Shifa; Quan, Jun; Tian, Chunhua; Gao, Guoying
Abstract : The eigenstate distribution of the HOMO and LUMO in the perylene-based device. Abstract : Carbon-based magnetic molecular junctions are promising candidates for nanoscale spintronic applications because they are atomically thin and possess high stability and peculiar magnetism. Herein, based on first-principles and non-equilibrium Green's function, we designed a carbon-based molecular spintronic device composed of carbon atomic chains, zigzag-edged graphene nanoribbon (ZGNR), and a perylene molecule. Our results show that the device exhibits integrated spintronic and spin caloritronic functionalities, such as the bias-voltage driven spin filtering effect, negative differential resistance effect and giant magnetoresistance, temperature-gradient driven spin Seebeck effect, thermal spin filtering effect, high thermal magnetoresistance, and thermal colossal giant magnetoresistance. Furthermore, considering the phonon vibration effect, the spin and charge thermoelectric figure of merits ( ZT sp and ZT ch ) can be enhanced and the peak of ZT sp is much larger than that of ZT ch, indicating the excellent thermospin performance. The asymmetrical contact configuration between the carbon atomic chain and perylene/ZGNR inhibits the phonon thermal conductivity significantly, leading to the optimal ZT sp and ZT ch of 2.4 and 0.5 at 300 K, respectively. These results suggest multifunctional spintronic and spin caloritronic applications for the perylene-based molecular device.